Impact of concomitant medications on the oncologic efficacy of systemic therapy in patients with advanced or metastatic urothelial carcinoma: a systematic review and meta-analysis - Tsuboi, Ichiro; Matsukawa, Akihiro; Parizi, Mehdi Kardoust; Miszczyk, Marcin; Fazekas, Tamás; Schulz, Robert J; Laukhtina, Ekaterina; Kawada, Tatsushi; Katayama, Satoshi; Iwata, Takehiro; Bekku, Kensuke; Rajwa, Pawel; et al. (BMC urology, 2025)
BACKGROUND: Immune checkpoint inhibitors (ICI) and chemotherapy, including antibody-drug conjugates, are widely used for the treatment of patients with advanced unresectable or metastatic urothelial carcinoma (UC). The majority of elderly patients receive concomitant medications to address various comorbidities. We aimed to evaluate the impact of concomitant medications on oncological outcomes in patients with advanced unresectable or metastatic UC treated with systemic therapy. MATERIAL & METHODS: In August 2024, three datasets were queried for studies evaluating concomitant medications in patients with advanced unresectable or metastatic UC. The review protocol was registered in PROSPERO (CRD42024547335). The primary outcome was overall survival (OS). A fixed- or random-effects model was used for meta-analysis depending on the heterogeneity. RESULTS: We identified 16 eligible studies (3 prospective and 13 retrospective) comprising 4,816 patients. Most reported concomitant medications included proton pump inhibitors (PPIs), antibiotics, steroids, and opioids. The use of concomitant PPIs, antibiotics, steroids or opioids during ICI therapy was associated with worsened OS (PPIs: HR: 1.43, 95% CI: 1.31-1.57, p < 0.001; antibiotics: HR: 1.2, 95% CI: 1.04-1.38, p = 0.01; steroids: HR: 1.45, 95% CI: 1.25-1.67, p < 0.001; and opioids: HR: 1.74, 95% CI: 1.46-2.07, p < 0.001). Concomitant use of antibiotics during chemotherapy did not impact OS (HR: 1.01, 95% CI: 0.67-1.51). CONCLUSIONS: When treating advanced unresectable or metastatic UC with ICI therapy, we need to pay attention to concomitant medications, such as PPIs and antibiotics to avoid reducing the efficacy of ICI therapy. The mechanism of action of these drugs on ICI efficacy requires further examination.
Keywords: Humans; Histamine type-2 receptor antagonists; karcinom z přechodných buněk; Urothelial carcinoma; urologické nádory; Antineoplastic Agents; inhibitory kontrolních bodů; výsledek terapie; lidé; Opioids; Antibiotics, steroids; Urologic Neoplasms; Neoplasm Metastasis; metastázy nádorů; Concomitant medications; Immune Checkpoint Inhibitors; Treatment Outcome; Carcinoma, Transitional Cell; protinádorové látky; Proton pump inhibitors; Immune checkpoint inhibitors